L'Homme-machine - La Mettrie, Julien Offray de 1709-1751; Assoun, Paul-Laurent -1948 (Paris Denoël Gonthier, 1981)
Man a Machine (French: L'homme Machine) is a work of materialist philosophy by the 18th-century French physician and philosopher Julien Offray de La Mettrie, first published in 1747. In this work, de La Mettrie extends Descartes' argument that animals are mere automatons, or machines, to human beings. He denies dualism and existence of the soul as a substance separate from matter.
Bibliography: p. [220]-222.
Keywords: Philosophy; Material culture